Twelfth Annual Signature Event, June 10, 2017, The Chisholm Trail [program and schedule of activities] (Symphony in the Flint Hills, 2017)
Program for the 2017 Symphony in the Flint Hills, with information about Deer Horn Ranch, artists, sponsors, and the schedule of activities, program notes, and a bio of guest artist Michael Martin Murphey, conductor Jason Seber, the Kansas City Symphony, and patrons.
Keywords: Michael Martin Murphey; Jason Seber; Kansas City Symphony